A COVID-19 necessity or the future of medical education? An evaluation of online psychiatry tutorials for medical students. (13th April 2021) - Wyke, C.; Butler, S.
Abstract : Introduction: Following the national lockdown in the UK in March 2020 in response to the COVID-19 pandemic, we instigated regular online tutorials for fourth year medical students undertaking their psychiatry placement. Objectives: The aims of these tutorials were threefold: to ensure that students covered a range of key psychiatry topics, to enable them to have the opportunity for interactive tutorials with experienced psychiatrists and, not least, to create a sense of continuity and connection with their tutors and peers across the mental health block. Methods: Each student was allocated to a tutorial group comprising 10 – 15 medical students and a psychiatrist facilitator. These groups met weekly for 7 consecutive weeks at an agreed time for 60 – 90 minutes via an online platform and all covered the same allocated topic each week. We evaluated these groups via an online survey sent to the students following the programme. Results: The students rated the tutorials on average as 4.5/5 on whether they met the defined learning outcomes. On average the students did not consider that the virtual format made a significant difference to their learning, but this disguised a wide range of views that were expressed via a comment box. Conclusions: The evaluation of this project supports the use of virtual tutorials as a valuable learning tool but educators need to be aware that student views' on these can be varied and so, long-term, a blend of virtual and face to face learning is most likely to meet the needs of all students.